The Gordian Knot : Political Gridlock on the Information Highway - Nancy H. Fontaine (Issues in Science and Technology Librarianship)
This article reviews the book The Gordian Knot : Political Gridlock on the Information Highway. Cambridge, Mass.: MIT Press, 1997, by W. Russell Neuman, Lee McKnight, and Richard Jay Solomon.